Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 11 - Rational Expressions and Functions - 11-5 Solving Rational Equations - Practice and Problem-Solving Exercises - Page 683: 30



Work Step by Step

Given: $(x+2)(x-1)=(x-2)(x+4)$ $x^2-x+2x-2=x^2+4x-2x-8$ $x^2+4x-2x-8-x^2+x-2x+2=0$ $2x-8+x-2x+2=0$ $x-6=0$ Hence, $x=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.